ANALISIS TATA LETAK BAHAN KIMIA PADA GUDANG PT. X MENGGUNAKAN METODE DEDICATED STORAGE - Meilizar, Meilizar; Wulandari, Fitri Aulia (Politeknik ATI Padang, 2017)
The problem faced by the Company is the absence of special arrangements applied to chemical warehouses in the storage or collection of warehoused products, so that the pattern of storage and the preparation of chemicals is randomized depending on the vacant warehouse position. Consequently longer transport times and long travel distances (there is a search process) and over pumping of goods. The purpose of this research is to get the design of chemical layout in the warehouse, to know the need of floor area and to know the total distance in the existing condition and the proposed condition. The method used is dedicated storage which is also called as a fixed storage plot for each product type. In this method the placement is based on the ratio of throughput and space requirement (T/S) with the largest T/S placed on the block with the distance between each block of smallest. From the calculation results obtained the total distance traveled at this time that is equal to 783.9 m and calculations on the proposed conditions obtained for 456.6 m, which means a decrease in total travel distance of 38.20%.